Association between Physical Activity, Body Composition, and Metabolic Disorders in Middle-Aged Women of Ksar el Kebir (Morocco) - Harraqui, Khouloud; Oudghiri, Dia Eddine; Mrabti, Hanae Naceiri; Hannoun, Zineb; Lee, Learn Han; Assaggaf, Hamza; Qasem, Ahmed; Goh, Khang Wen; Long, Chiau Ming *; Tan, Ching Siang; Bouyahya, Abdelhakim; Bour, Abdellatif (MDPI, 2023)
This study aimed to examine the association between physical activity (PA), body composition, and metabolic disorders in a population of Moroccan women classified by menopausal status. This cross-sectional study comprised 373 peri- and postmenopausal women aged 45–64 years old. PA levels were assessed using the short version of the International Physical Activity Questionnaire (IPAQ-SF). Body composition and metabolic disorders were assessed by measurements of anthropometric and biological parameters: weight, body mass index (BMI), waist circumference (WC), hip circumference (HC), WC/HC ratio, percent body fat, systolic and diastolic blood pressure, fasting blood glucose, and serum lipids (total cholesterol (TC), triglycerides (TG), HDL-C, and LDL-C). Metabolic syndrome (MetS) was diagnosed according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) criteria. Pearson correlations were used to test for associations. The mean total PA score of perimenopausal women was 1683.51 ± 805.36 MET-min/week, and of postmenopausal women was 1450.81 ± 780.67 MET-min/week. In all participants, peri- and postmenopausal women, PA was significantly and inversely associated with BMI, weight, percent body fat, HC, WC, and number of MetS components (p < 0.01), and with fasting blood glucose, TC, TG, and LDL-C (p < 0.05). The frequencies of metabolic disorders, obesity, abdominal obesity, type 2 diabetes, dyslipidemia, and MetS were significantly lower at moderate and intense levels of PA (p < 0.05), in also all participants. In middle-aged women, particularly those who are peri-menopausal, PA at moderate and intense levels is associated with more favorable body composition and less frequent metabolic disorders. However, in this particular study, PA does not appear to be associated with blood pressure and HDL-C concentrations. Future studies may be needed to further clarify these findings.